Exploration of Curcumin against Various Biological Disorders: Mechanism of Action and Pharmacotherapeutics - Kumar, Mritunjay; Verma, Swati; Malviya, Rishabha; Sundram, Sonali; Sharma, Akanksha; Mishra, Neelesh (Natural Products Journal, The, 2023)
Synthetic drug usage has risen substantially, although plant-based medicines are more appropriate in terms of adverse effects. Through the classical era, humans relied on Phyto moieties to cure several illnesses, the most common of which is curcumin, the main phenol derived from the various varieties of turmeric. Its therapeutic and medicinal qualities are described in the Vedic Scriptures and Chinese medicine. Curcumin has been widely researched for its pleiotropic action, which includes anti-inflammatory, and anti-oxidant properties. The manuscript aims to describe the sources, properties, and pharmacological activities of curcumin. Turmeric is grown in India, and curcumin is a major phytoconstituent of turmeric. It has pharmacological activities like anti-oxidant, analgesic, anticarcinogenic, chemo-preventive, anti-inflammatory, chemo-therapeutic, antifungal, antibacterial, antitumor, neuroprotective, anti-diabetic, anti-apoptotic, and immunomodulatory activities. Curcumin has been recommended in various research to have anti-cancer effects on several biochemical pathways associated with metastatic disease, cell cycle regulation, and so on. It can be concluded from the findings of the pieces of literature that curcumin is an important phytoconstituent and has the potential to treat various biological disorders. Curcumin’s anti-tumor efficacy is the most prominent research activity being carried out by researchers worldwide. In the present review, the authors have summarized the important pharmacological activities of curcumin, and the mechanism of action involved to forecast the pharmacotherapeutic effect like for anti-cancer effects (suppression of NF-KB, intrinsic and extrinsic pathways, PKC inhibition and many more), for anti-viral effect (Interfering Genomic Replication, Inhibiting Virus attachment, Activation of cellular signaling Pathways, etc.), for Anti-diabetic (AMPK activation, Decreased liver fat deposition, etc.), for neuroprotective effect (Increased p-Akt and p-mToR levels, Reducing p-p338, LC-II/LC-I, p-38 levels, etc.) and for other activities also like antibacterial, immunomodulatory, anti-inflammatory and anti-oxidant.
Keywords: anti-inflammatory